The Representation of Environmental Knowledge in Javanese Proverbs: An Ecolinguistic Study - Elisa, Veny; Subiyanto, Agus (Proceedings International Conference of Culture and Sustainable Development; Vol 3 (2025): PROCEEDINGS ICOCAS, 2025)
Proverbs often emerge from the lived experiences of a community, including its ecological setting, subsistence activities, biological resources, and cultural interactions with plants, animals, and natural processes. This study explores the representation of environmental knowledge embedded in Javanese proverbs from an ecolinguistic perspective. As a form of oral tradition, Javanese proverbs reflect the worldview, values, and ecological awareness of the community, particularly in relation to their agrarian way of life and close interaction with nature. The data used in this study are taken from books on Javanese proverbs, and online sources discussing Javanese proverbs. To collect the data, we use an observation method, with a note taking technique. Using qualitative content analysis, this research will identify how Javanese proverbs convey ecological wisdom through metaphors drawn from plants, animals, abiotic environment, natural phenomena, and farming activities. The findings will reveal that these proverbs encode not only traditional environmental knowledge but also promote values such as harmony with nature, sustainability, and intergenerational responsibility. By examining these linguistic expressions through the approach of ecolinguistics, the study will highlight the role of language in preserving indigenous ecological perspectives and reinforcing environmentally ethical behavior within the Javanese cultural context.
Keywords: Javanese proverbs, environmental knowledge, ecolinguistics